Stroke and Large Vessel Occlusion Risk According to Cincinnati Prehospital Stroke Scale Symptom Patterns in a CPSS-Positive EMS Cohort: A Prospective Cohort Study - Filippo Bernasconi; Lorenzo Querci; Michela Generali; Lucia Taurino; Filippo Galbiati; Mariangela Piano; Paola Manzoni; Riccardo Stucchi; Maurizio Migliari; Giuseppe Ristagno; Arturo Chieregato (Journal of Clinical Medicine, 2026)
Background: The absolute risk and risk ratio of stroke and large vessel occlusion (LVO) across different Cincinnati Prehospital Stroke Scale (CPSS) categories and symptom patterns remain incompletely defined. This study quantified stroke and LVO risk across CPSS categories, symptom patterns, and predefined CPSS groupings. Methods: This single-center prospective observational study included consecutive adults patients assessed by basic life support (BLS) emergency medical service crews in the Milan metropolitan area between March 2023 and December 2024. Patients were eligible if they had a prehospital stroke code based on CPSS ≥ 1, symptom onset within 24 h, a pre-stroke modified Rankin Scale score ≤ 3, and transport to Grande Ospedale Metropolitano Niguarda, a comprehensive stroke center (CSC). Final diagnoses were obtained from hospital records and neuroimaging. Absolute risks and risk ratios for stroke, ischemic stroke, and LVO were calculated across predefined CPSS categories. Discrimination was assessed using receiver operating characteristic analysis. Results: Among 876 patients, 411 (47%) had ischemic stroke, 96 (11%) intracerebral hemorrhage, and 164 (19%) LVO. The observed proportion of patients with stroke increased from 41% among those with CPSS = 1 to 78% among those with CPSS = 3, while the corresponding proportion with LVO increased from 6% to 36%. Risk ratios showed a similar gradient. Among patients with CPSS = 2, differences between symptom patterns were small. For LVO, the difference in discrimination between CPSS = 3 and the predefined grouping including CPSS = 3 or CPSS = 2 with Face and Arm deficits was small. Overall, these findings were more consistent with a severity gradient than with superiority of a specific symptom pattern or predefined CPSS grouping. Discrimination across the evaluated CPSS categories and predefined CPSS groupings was limited to modest. Conclusions: In CPSS-positive stroke-code patients assessed by BLS crews and transported to a single CSC, higher CPSS scores were associated with progressively higher observed proportions of stroke and LVO. These estimates are conditional on the study cohort and require external validation. They should therefore not be used alone to define transport pathways or guide clinical management.